Building a Resilient Generation: Education as a Bulwark Against Student Radicalism in Senior High Schools in Tangerang Regency - Suryadi; Ecep Isak Fariduddin (International Research and Development for Human Beings (IRDH), 2025)
Tangerang Regency, as a region with social diversity, faces challenges in countering radicalism among students. This article discusses the results of community service activities implemented through seminars in high schools in 2025. These activities aimed to provide students with an understanding of the dangers of radicalism and strategies for preventing it through balanced education. The seminar material was delivered using interactive lectures, discussions, and question-and-answer sessions involving students and teachers. The results showed an increase in students' knowledge regarding the definition of radicalism, causal factors, early indicators, and preventive measures in the school environment and on social media. School support and the active role of teachers are key factors in maintaining students' ideological resilience. This article recommends strengthening educational programs for preventing radicalism periodically in high schools in Tangerang Regency.